Persepsi Pendidik Anak Usia Dini Terhadap Integrasi Teknologi di Kecamatan Lotu Kabupaten Nias Utara - Rosfalia, Nihna Atho'a; Ikha Durrotun Nasikhah; Firman Priyo Suhasto (Institut Nalanda, 2024)
The use of technology can be integrated into early childhood education up to college. Several studies explain that technology can improve the learning process in early childhood education. This study aims to investigate teachers' perceptions of technology integration into early childhood learning. This study uses a descriptive-qualitative method that applies a case study as a research design. The data obtained are primary data. The research instruments consisted of observations, interviews, and surveys in which teachers of the Pelangi Early Childhood Education School in Lotu District, North Nias Regency became research respondents. The results of the study showed that most teachers showed a positive attitude towards the use of technology in the classroom and had tried to integrate it into learning activities. Meanwhile, there are two obstacles in implementing technology in learning for early childhood, namely maintaining their attention when using technological devices in the classroom and choosing technology that is appropriate for children. The use of technology in learning can motivate, make learning more fun, child-centered learning, and increase children's opportunities to achieve learning targets